Der Peloponnesische Krieg : griechisch-deutsch - Thucydides (Sammlung Tusculum, 2017)
"Thucydides regarded his unfinished work on the Peloponnesian War as a "possession for all time." This edition offers a new translation that is more faithful to the uniqueness of the original text while at the same time remaining closer to contemporary German than previous versions. The volume includes a detailed introduction and explanatory comments."--Provided by publisher